SOCIO-PHILOSOPHICAL SIGNIFICANCE OF PHYSICAL EDUCATION AND SPORTS IN THE HEALTH OF THE MAID-DEVELOPED GENERATION - Nilufar Niyozova, (Central Asian Journal of Medicine, 2023)
This article is devoted to the basics of the health of children and adolescents, a description of the socio-philosophical significance of sports is given, as well as a scientific and practical classification of experience.